1984
DOI: 10.1136/bmj.289.6447.717
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric bacterial activity and nitrosation before, during, and after treatment with omeprazole.

Abstract: Ten healthy volunteers were studied before, during, and after treatment with omeprazole 30 mg daily for two weeks. On the 14th night mean nocturnal (2100-0700) intragastric acidity was significantly decreased by 75%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(91 citation statements)
references
References 16 publications
7
82
0
2
Order By: Relevance
“…Our data demonstrate that suppression of gastric acid would permit the survival of germinated C. difficile cells. This finding is consistent with the results of other studies correlating reduced acidity (pH Ͼ 3) and increased bacterial growth in gastric contents from people taking PPIs (10,23,25,26). Because conditions in the stomach are not as anaerobic or reduced as in the colon, the ability of vegetative C. difficile to survive under aerobic conditions could also facilitate the survival of germinated spores in the stomach.…”
Section: Discussionsupporting
confidence: 82%
“…Our data demonstrate that suppression of gastric acid would permit the survival of germinated C. difficile cells. This finding is consistent with the results of other studies correlating reduced acidity (pH Ͼ 3) and increased bacterial growth in gastric contents from people taking PPIs (10,23,25,26). Because conditions in the stomach are not as anaerobic or reduced as in the colon, the ability of vegetative C. difficile to survive under aerobic conditions could also facilitate the survival of germinated spores in the stomach.…”
Section: Discussionsupporting
confidence: 82%
“…The fact that patients with pernicious anemia, invariably associated with gastric atrophy and hypochlorhydria, have an increased risk of developing stomach cancer [52,53] has raised the question of whether therapeutic hypochlorhydria is carcinogenic to the stomach. Pharmacologically induced hypochlorhydria has been shown to be associated with increased gastric bacterial growth, reduction of nitrate to nitrite, and increased concentration of carcinogenic N-nitroso compounds in the gastric juice [54,55]. Some studies have indicated that long-term treatment with PPIs may accelerate the development of atrophic changes of the gastric mucosa in individuals infected with H. pylori [56 -58].…”
Section: Medical Therapy For Peptic Ulcer and Its Relation To Stomachmentioning
confidence: 99%
“…H. pylori survives in the human stomach at low pH (pH Ͻ 3) by creating an alkaline microenvironment with urease production (21). Although Acinetobacter has variable urease activity, this bacterial species has been reported previously to colonize the hypochlorhydric stomach of patients (32,39). In addition, the mouse stomach, which has a gastric acidic range of approximately 3 to 5 eq, provides an environment permissive for colonization by non-H. pylori organisms (42).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these animals were clearly colonized with Since it has recently been shown that Toll-like receptor 9 (TLR-9) mediates a Th1 inflammatory response from bacterial DNA (10), it is highly possible that the presence of Acinetobacter DNA in the gut was sufficient to induce gastritis, but this requires further analysis. Acinetobacter has been previously isolated from the gastric contents of patients treated with proton pump inhibitors and is clinically relevant in humans (32). Both A. baumannii and A. lwoffii are known to cause nosocomial infections in ventilated patients (8).…”
Section: Discussionmentioning
confidence: 99%